Meeting the Needs of Patient Preferences in Imaging - Hayatghaibi, Shireen E; Trout, Andrew T; Wright, Davene R (Academic radiology, 2024)
Healthcare continues to transition toward a patient-centered paradigm, where patients are active in medical decisions. Fully embracing this new paradigm means updating how clinical guidelines are formulated, accounting for patient preferences for medical care. Recently, several societies have incorporated patient preference evidence in their updated clinical practice guidelines, and patients in their expert panels. To fully transition to a patient-centered-paradigm, imaging organizations should rethink the formulation of clinical guidelines, accounting for patient preference evidence.